Diri: Satu Pemahaman Falsafah Muhammad Iqbal dalam Asrari-Khudi - Siren, Nor Raudah (Jurnal Usuluddin, 2001)
This article tries to understand the philosophy of self of Muhammad Iqbal (1207-1273) based on the Malay version his important poem, Asrari-Khudi (Secret of Self).